Ismail Xavier - uma representação - Fernandes, Gabriel Marques (Albuquerque (online), 2022)
LUNARDELLI, Fatimarlei; SILVA, Humberto Pereira da; PINTO, Ivonete (orgs.). Ismail Xavier: um pensador do cinema brasileiro. São Paulo: Edições Sesc São Paulo, 2019